Caracterização petrográfica estrutural e metamorfica das rochas da região de Indiara (GO) - Fumes, Regiane Andrade [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The region Indiara (GO) is located in southwestern of São Francisco Craton in the Internal Zone of the Brasília Belt, western part of the Tocantins Province. In this locality outcrop rocks of the Goiás Magmatic Arc. These rocks are muscovite gneiss with biotite, muscovite-biotite gneiss, biotite gneiss with muscovite and garnet, biotite-muscovite gneiss, muscovite porfiroclastic gneiss, biotite porfiroclastic gneiss, muscovite-quartz schists, garnetquartz schists, and metamafic rock (hornblende schists) as metric or kilometric lenses. The gneisses have granodioritic composition, granoblastic texture, with some portions with lepidoblastic texture, constituting a discontinuous centimeter to millimeter banding; the structure is anisotropic, marked by the preferred orientation of all the minerals. These gneisses are leucocratic, generally are inequigranular and fine to medium grained. The hornblende schists have nematoblastic texture, are inequigranular and fine to medium grained and have anisotropic structure that is given by a foliation, marked by a strong preferential orientation of the crystals of amphibole and other minerals present in the rock. The gneisses of the area are composed of plagioclase (oligoclase/andesine), quartz, microcline, muscovite, biotite, epidote, apatite, zircon, garnet, kyanite, oxides and hydroxides of iron and opaque minerals. And the metamafic rocks of Indiara region are composed mainly of amphibole, plagioclase (oligoclase/andesine), quartz, titanite, biotite, allanite, garnet, oxides and hydroxides of iron, apatite, epidote, rutile, muscovite and opaque minerals. At least three phases of deformation were observed in the rocks of area of study (Dn-1, Dn and Dn +1). The Dn phase and represented by a well-marked foliation Sn having low dip angle (average dip of 20 °) and dip direction to SW (210/21) and to NE (18/20); the Dn-1 phase is represented by a compositional banding (Sn- 1), this banding is generally...

A região de Indiara (GO) situa-se no sudoeste do Cráton São Francisco na Zona Interna da Faixa Brasília, porção ocidental da Província do Tocantins. Nesta localidade aflora o Arco Magmático de Goiás que é representado pelas seguintes rochas: muscovita gnaisse com biotita, biotita-muscovita gnaisse, biotita gnaisse com muscovita e granada, biotitamuscovita gnaisse e muscovita gnaisse porfiroclástico, biotita gnaisse porfiroclástico, muscovita-quartzo xisto e granada-quartzo xisto, além de rocha metamáfica (hornblenda xisto). Os gnaisses possuem composição granodoirítca, textura granoblástica, com algumas porções com textura lepidoblástica, constituíndo um bandamento descontínuo, centimétrico a milimétrico; a estrutura é anisotrópica, marcada pela orientação preferencial dos minerais constituintes das rochas. Os gnaisses são leucocráticos, geralmente inequigranulares, de granulação fina a média O hornblenda xisto apresenta textura nematoblástica, inequigranular e granulação fina a média, a estrutura é anisotrópica dada por uma xistosidade, marcada por uma forte orientação preferencial dos cristais de anfibólio e dos demais minerais presentes na rocha. Os gnaisses da área são compostos por plagioclásio (oligoclásio/andesina), quartzo, microclínio, muscovita, biotita, epidoto, apatita, zircão, granada, cianita, óxidos e hidróxidos de ferro e minerais opacos. Já as rochas metamáficas da região de Indiara são compostas por anfibólio, plagioclásio (oligoclásio a andesina), quartzo, titanita, biotita, allanita, granada, óxidos e hidróxidos de ferro, apatita, epidoto, rutilo, muscovita e minerais opacos. Ao menos três fases deformacionais foram observadas nas rochas da área (Dn-1, Dn e Dn+1). A fase Dn é representada por uma foliação bem marcada Sn que possui baixo ângulo de mergulho (mergulho médio de 20º) e caimento para SW (210/21) e para NE (18/20); já a fase Dn-1 é representada...
Keywords: Geologia estrutural; Rochas metamorficas; Geoquimica; Petrologia; Gnaisse; Indiara (GO)